THE MULTIDIMENSIONALITY FOREIGN DIRECT INVESTMENT’S IMPACT ON THE ECONOMY - Emmanuel Imuede Oyasor (Gusau Journal of Accounting and Finance)
Foreign direct investment (FDI) has been a crucial inflow source for many economies. The contribution of FDI to growth has continued to generate extensive debates. The debate centered on channels through which FDI may enhance technological diffusion through spillover effect of knowledge and new capital goods to better human conditions. In this direction, some earlier literatures have also argued that the contribution of FDI largely dependent on the circumstances in the recipient countries. The study follows the endogenous growth model theory and eclectic theory to demonstrate the multidimensionality impacts of FDI inflows on gross domestic product (GDP), human capital development/utilization (HCDU), national revenue generation (NRG), gross fixed capital formation (GFCF) and gross national savings (GNS), based on published information over the period of 1982 to 2022. We found that FDI have significant effect on GDP; FDI do significantly affect on human capita development/utilization; FDI has no significant impact on NRG; FDI has no have no significant connection with gross fixed capital formation and FDI have significant effect on gross national savings in Nigeria.